2010
DOI: 10.1152/physiolgenomics.00167.2009
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences between smoking-related gene expression in nasal and bronchial epithelium

Abstract: Previous studies have shown that physiological responses to cigarette smoke can be detected via bronchial airway epithelium gene expression profiling and that heterogeneity in this gene expression response to smoking is associated with lung cancer. In this study, we sought to determine the similarity of the effects of tobacco smoke throughout the respiratory tract by determining patterns of smoking-related gene expression in paired nasal and bronchial epithelial brushings collected from 14 healthy nonsmokers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 24 publications
8
104
1
1
Order By: Relevance
“…Airway epithelial cells represent a promising biospecimen for studying COPD, as molecular profiles in minimally invasively collected tissue specimens will be needed if these biomarkers are to ultimately translate into the clinic. Beyond the potential of bronchial epithelium, which we have highlighted in this review, recent work suggests that gene expression signatures in nasal and buccal epithelium may serve as surrogates for the bronchial airway response to cigarette smoke (29,30), and future studies should evaluate whether COPDassociated gene expression changes can also be identified at these readily accessible sites. Technologic advances, such as single-cell sequencing (51), also hold the potential to improve characterization of disease heterogeneity by providing a detailed portrait of disease-associated processes occurring in different cell types within a tissue and the heterogeneity of those processes between different cells of the same cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Airway epithelial cells represent a promising biospecimen for studying COPD, as molecular profiles in minimally invasively collected tissue specimens will be needed if these biomarkers are to ultimately translate into the clinic. Beyond the potential of bronchial epithelium, which we have highlighted in this review, recent work suggests that gene expression signatures in nasal and buccal epithelium may serve as surrogates for the bronchial airway response to cigarette smoke (29,30), and future studies should evaluate whether COPDassociated gene expression changes can also be identified at these readily accessible sites. Technologic advances, such as single-cell sequencing (51), also hold the potential to improve characterization of disease heterogeneity by providing a detailed portrait of disease-associated processes occurring in different cell types within a tissue and the heterogeneity of those processes between different cells of the same cell type.…”
Section: Discussionmentioning
confidence: 99%
“…The airway field of injury hypothesis, initially established in the setting of cigarette smoke exposure, posits that toxins and carcinogens from cigarette smoke bathe the entire respiratory tract. This exposure leads to measurable alterations in the small airway epithelium (28), large airway epithelium (27), and epithelium of the nose and mouth (29,30). A diseasespecific airway field of injury has been described in the setting of lung cancer, where gene expression profiling of the cytologically normal airway epithelium distal from the lung tumor can serve as a sensitive and specific biomarker of lung cancer (31) that performs independently of other clinical variables (32).…”
Section: Airway Gene Expression Reflects Genomic Alterations Within Tmentioning
confidence: 99%
“…Derzeit ist jedoch noch keiner dieser Biomarker oder Risikogene zur klinischen Anwendung geeignet [10]. Experimentelle Ansätze konnten zeigen, dass Genanalysen des Nasalepithels von Rauchern als Surrogatparameter dienen könnten, um den schadhaften Effekt des Rauchens auf die Lunge zu beurteilen [30]. Die Entwicklung von Biomarkern und Risikogenen tritt somit zunehmend in den Fokus der Forschung, und die laufenden Screeningstudien könnten beitragen, hier in den kommenden Jahre weitere Fortschritte zu erzielen [8,9].…”
Section: Bach/spitzunclassified
“…Bhutani et al further supported this conclusion when they found a strong correlation between bronchial and oral tissue in the degree of p16 and FHIT promoter methylation at baseline and 3 months after intervention in 127 smokers enrolled in a randomized placebo-controlled chemoprevention trial (18,19); this rather specific study, however, did not profile global epigenetic changes in the bronchi and oral cavity. More recent analyses of genome-wide gene expression profiling of matched nasal and bronchial epithelium showed that the majority of gene expression consequences of smoking are common to both nasal and bronchial epithelium, suggesting that nasal epithelial gene expression may serve as a relatively noninvasive surrogate measure of physiologic responses to cigarette smoke in the lower airway (20).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic profiling of matched upper and lower airway cells from the same individual (versus from unrelated individuals) is needed to fully characterize the ability of the mouth to serve as a surrogate for the bronchus (18,20). Further study of buccal sampling methods is also needed.…”
Section: Introductionmentioning
confidence: 99%